A Debreceni egyetem nyolcvanéves Főépülete (Három rövid beszéd) - Fényi, Tibor; Gesztelyi, Tamás (Gerundium, 2012)
THE MAIN BUILDING OF THE UNIVERSITY OF DEBRECEN IS EIGHTY YEARS OLD: THREE SHORT SPEECHES. The first speech was delivered by Tibor Fényi, Director of the Miksa Róth Museum, on February 3, 2012, in the State Assembly Hall of the Main Building, on the occasion of celebrating the restoration of the ornamental stained-glass windows of the Assembly Hall. hematically linked with the irst one, the second speech, given on March 15, 2012, by Tamás Gesztelyi, Professor of Latin Studies and Art History introduced a volume jointly produced by photographer József Hapák and Secretary-General of the University Mónika Rői, on the subject of the stained-glass windows, appreciating the windows from the angle of art history. he third speech was also delivered by Professor Tamás Gesztelyi; this speech was delivered on May 15, 2012, at the opening ceremony of a photo exhibition arranged by Professor of Geography Péter Csorba, entitled he spirit of the place: our main building is 80 years old.